Factors influencing the purchase of gadget - Thuraisyah Jaaffar, . (2012)
This research was intended to review the factors that influence the purchase of gadget. The factors that used to analyze in this research are; customer motivation, brand name, product design and price. Hence, to analyze these factors, researcher had used coefficient correlation to determine which factor had high tendency towards the dependent variable (purchase of gadget). Customer motivation factor explain about the environment that influence them to attempt a purchase like; media, friends and customer confident level. The coefficient correlation value for the customer motivation factor is positive .490, which indicates weak relationship. Besides that, brand name factor also play the vital role to influence the purchase of gadget. Usually, the good reputation of a brand attracts customer to buy most. The coefficient correlation value for the brand name factor is positive .338, which indicates weak relationship. Next, product design factor explain the characteristic of a product, specification, application and function. The coefficient correlation value for the product design factor is positive .575, which indicates moderate relationship. The last factor that had been tested is price. The coefficient correlation value for the price factor is positive .279, which indicates very weak relationship. This value was obtained from coefficient correlation between the dependent variable (purchase of gadget) compare to others factors. This may due to the price factor is no longer customer concern as long they had the intention to buy.